Synthesis by gamma irradiation of hyaluronic acid-polyvinyl alcohol hydrogel for biomedical applications - Godoy-Alvarez, Fernanda Kamila; González-Torres, Maykel; Giraldo-Gomez, David M.; Sánchez-Sánchez, Roberto; Pérez-Díaz, Mario A.; González-Del Carmen, Manuel; Figueroa-González, Gabriela; Reyes-Hernández, Octavio D.; Sharifi-Rad, Javad; Cortés, Hernán; Del Prado-Audelo, María Luisa; Leyva-Gómez, Gerardo (Cellular and Molecular Biology, 2021)
Hyaluronic acid (HA) is one of the most attractive natural polymers employed in biomaterials with biological applications. This polysaccharide is found in different tissues of the body because it is a natural component of the extracellular matrix; furthermore, it has crucial functions in cell growth, migration, and differentiation. Since its biological characteristics, HA has been utilized for the new biomaterial's development for tissue engineering, such as hydrogels. These hydrophilic macromolecular networks have gained significant attention due to their unique properties, making them potential candidates to be applied in biomedical fields. Different mechanisms to obtain hydrogels have been described. However, the research of new non-toxic methods has been growing in recent years. In this study, we prepared a new hydrogel of HA and polyvinyl alcohol by the cost-effective technique of cross-linking by gamma irradiation. The hydrogel was elaborated for the first time and was characterized by several methods such as Fourier Transform Infrared Spectroscopy, Differential Scanning Calorimetry, Thermogravimetric Analysis, and Scanning Electron Microscopy. Likewise, we evaluated the cytotoxicity of the biomaterial and its influence on cell migration in human fibroblasts. Furthermore, we provide preliminary evidence of the wound closure effect in a cellular wound model. The novel hydrogel offers an increase of HA stability with the potential to expand the useful life of HA in its different medical applications.